Enhancing disaster risk resilience using greenspace in urbanising Quito, Ecuador - C. S. Watson; J. R. Elliott; S. K. Ebmeier; M. A. Vásquez; C. Zapata; S. Bonilla-Bedoya; P. Cubillo; D. F. Orbe; M. Córdova; J. Menoscal; E. Sevilla (Natural Hazards and Earth System Sciences, 2022)
Greenspaces within broader ecosystem-based disaster risk reduction (Eco-DRR) strategies provide multiple benefits to society, biodiversity, and addressing climate breakdown. In this study, we investigated urban growth, its intersection with hazards, and the availability of greenspace for disaster risk reduction (DRR) in the city of Quito, Ecuador, which experiences multiple hazards including landslides, floods, volcanoes, and earthquakes. We used satellite data to quantify urban sprawl and developed a workflow incorporating high-resolution digital elevation models (DEMs) to identify potential greenspaces for emergency refuge accommodation (DRR greenspace), for example, following an earthquake. Quito's historical urban growth totalled ∼ 192 km2 for 1986–2020 and was primarily on flatter land, in some cases crossed by steep ravines. By contrast, future projections indicate an increasing intersection between easterly urbanisation and steep areas of high landslide susceptibility. Therefore, a timely opportunity exists for future risk-informed planning. Our workflow identified 18.6 km2 of DRR greenspaces, of which 16.3 km2 intersected with potential sources of landslide and flood hazards, indicating that hazard events could impact potential “safe spaces”. These spaces could mitigate future risk if designated as greenspaces and left undeveloped. DRR greenspace overlapped 7 % (2.5 km2) with municipality-designated greenspace. Similarly, 10 % (1.7 km2) of municipality-designated “safe space” for use following an earthquake was classified as potentially DRR suitable in our analysis. For emergency refuge, currently designated greenspaces could accommodate ∼ 2 %–14 % (depending on space requirements) of Quito's population within 800 m. This increases to 8 %–40 % considering all the potential DRR greenspace mapped in this study. Therefore, a gap exists between the provision of DRR and designated greenspace. Within Quito, we found a disparity between access to greenspaces across socio-economic groups, with lower income groups having less access and further to travel to designated greenspaces. Notably, the accessibility of greenspaces was high overall with 98 % (2.3 million) of Quito's population within 800 m of a designated greenspace, of which 88 % (2.1 million) had access to potential DRR greenspaces. Our workflow demonstrates a citywide evaluation of DRR greenspace potential and provides the foundation upon which to evaluate these spaces with local stakeholders. Promoting equitable access to greenspaces, communicating their multiple benefits, and considering their use to restrict propagating development into hazardous areas are key themes that emerge for further investigation.